How would you solve these? (I use your explanations and answers as reference to my homework, because the summer teacher is out of reach oustide of class).
1) find an explicit general solution of the differential equation:
y' - 2xy= e^(x^(2))
2) Find an explicit general solution of the differential equation:
xy'= 2y + x^(3) cosx
3) Find an explicit general and particular solution of the initial value problem:
xy' - y= x, y(1)= 7
4) Find an explicit general and particular solution of the initial value problem:
y' + y= e^(x), y(0)= 1
5) A 400-gal tank initially contains 100 gal of brine (salt water) containing
50 lb of salt. Brine containing 1 lb of salt per gallon enters the tank at
the rate 5 gal/s, and the well-mixed brine in the tank flows out at the rate
of 3 gal/s. How much salt will the tank contain when it is full of brine?
(Solve questions using linear first order equation method primarily.
If you have any other methodic approaches to this problem, please
feel free to demonstrate).
At time t there's 100+2t gallons of brine in the tank. So5) A 400-gal tank initially contains 100 gal of brine (salt water) containing
50 lb of salt. Brine containing 1 lb of salt per gallon enters the tank at
the rate 5 gal/s, and the well-mixed brine in the tank flows out at the rate
of 3 gal/s. How much salt will the tank contain when it is full of brine?
(Solve questions using linear first order equation method primarily.
If you have any other methodic approaches to this problem, please
feel free to demonstrate).
Integrating factor:
Integrate and get:
Using the IC that t(0)=50, we get
The tank is full when 100+2t=400, t=150
Please check my calculations. Easy to go astray.
I still did not understand it your explanation. This is what I did to Find the general equation... Is this correct? If not could someone please help me with this?
y'+ p(x) y= Q(x) p(x)= -2x
y'- 2xy = e^(x*x) Q(x)= e^(x*x)
v(x)= e^(Int p(x) dx) = e^ (Int -2x dx)= e^(-x^(2))
y(x)= Int v(x)Q(x)+c
v(x)
y(x)= Int e^(-x^(2)) * e^(x*x) + c
(e^(-x^(2)
= e^(-x^(2)) * 1/2 e ^(x*x) +c
e^(-x^(2))
G.S. ==> Y(x)= 1/2 e^(x*x) + c
e^(-x^(2))